Relationships between PutraLMS successful factors, motivation to learn, and selfregulated learning strategies among undergraduate students in a Malaysian Public University - Hashemyolia, Shayesteh (2015)
Learning management system (LMS) as a supplementary tool is widely utilize in face to face classroom to enhance students’ learning. The higher education institutions in Malaysia integrates LMS to increase learning quality. The main objective of this study is to identify the relationship between PutraLMS successful factors, motivation to learn, and use of self-regulated learning strategies (SRLS) among undergraduate students who used LMS as technology enhanced learning in a blended learning environment. In order to achieve the objectives, this study used quantitative survey research method to measure the individual attitudes and opinions toward some issues, identify relationships among variables, and interpret their behaviour. Undergraduate students in Universiti Putra Malaysia (UPM) were chosen as population of the study since UPM has a long history in implementing LMS in teaching and learning in variety of courses. This study used stratified random sampling technique. Thus, three faculties in science and three faculties in social science were randomly selected. 365 questionnaires were distributed in May 2013, with a total of 282 questionnaires collected and usable for data analysis. This study used questionnaire of the perceived LMS interactivity, usefulness, and satisfaction based on two model as Three Tier Model (TTM) and DeLone and McLeen model (D&M). Moreover, for assessing the students’ motivation to learn and use of self-regulated learning strategies, this study used Motivated Strategies for Learning Questionnaire (MSLQ). This study considered students’ motivation to learn and use of self-regulated learning strategies in terms of five factors; namely intrinsic goal orientation, task value, self-efficacy, metacognitive and resource management strategies. The resource management strategies include time and environment management, effort regulation, help seeking and peer learning. The questionnaire reliability was tested in pilot study and validity was checked by a group of expert panel. The data assumptions (normality, linearity, collinearity, and outliers) were met threshold value before inferential statistical analysis. The descriptive result showed that (i) The students evaluated PutraLMS in high level in terms of interactivity, satisfaction, and usefulness. The students’ motivation to learn and use of self-regulated learning strategies were in moderate level. (ii) The result of structural equation modeling (SEM) of testing hypothesis in LMS successful model of study, showed that interactivity is significantly related to usefulness (β=.466) and satisfaction (β=.476). Moreover, there was significant relationship between satisfaction and usefulness (β=.380). (iii) Students’ perception towards LMS predicted students’ motivation to learn with different standard regression weight. In this case, motivation to learn was significantly more influenced by perceived usefulness with (β=.480) compared with perceived satisfaction (β=.253). (iv) The findings of this study revealed that students’ motivation to learn significantly related to the students’ usage of metacognitive (β=.643) and resource management self-regulated learning strategies (β=.498). (v) The result of mediation test of bootstrap result showed that satisfaction has an important role in relationship between interactivity and usefulness (β=.46). Moreover, perceived satisfaction had a direct and indirect effect on motivation to learn. The result indicated that indirect effect of satisfaction on motivation to learn is partially mediated by usefulness (β=.24). Finally, the statistical analysis of mediation model shows that motivation to learn as the third variable facilitated the relationship between perceived satisfaction of LMS and use of self-regulated learning strategies (β=.21). According to the findings, three mediation variables (perceived usefulness, satisfaction, and motivation to learn) partially mediated the relationship between independent and dependent variables. The implications obtained from the results of this study supports Social Cognitive Theory that predicting a wide range of variables influencing students’ use of SRLS in blended learning environment. Theoretically, this study indicated that LMS as a part of face to face course plays an important role in the students’ motivation to learn and use of SRLS. Accordingly, motivated learners take more responsibility for their learning to be successful. As a conclusion of this study, motivation to learn plays a central role on the relationship between students’ use of SRLS and perceived LMS usefulness. Thus, these two variables must be taken into account in formulating education policy, in order to help students use the SRLS effectively and enhance efficiency of LMS in education.